2015
DOI: 10.1002/hep.27555
|View full text |Cite
|
Sign up to set email alerts
|

Differential osteopontin functions: The role of osteopontin isoforms

Abstract: We would like to thank Dr. Fujita for the positive comments. We agree that a sensitivity of 67% and specificity of 96% would be useful as a test used in the clinic. 1 In regard to cost, we also agree that this is a very important consideration, along with complexity of the test and feasibility for a clinical laboratory to perform the test. These were considerations that we contemplated throughout the development of the project. For example, at an earlier stage of the project, we experimented with a quicker, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…iOPN is a cytoskeletal protein that plays a significant role in the regulation of the intracellular protein functions, while sOPN acts as a cytokine . Also, it is proposed that iOPN contributes to protection and sOPN is involved in promotion of the disease . The last but not the least possible reason is that OPN expression is predominant in areas with active fibrogenesis and where myofibroblasts are accumulated, as confirmed by the histological analysis .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…iOPN is a cytoskeletal protein that plays a significant role in the regulation of the intracellular protein functions, while sOPN acts as a cytokine . Also, it is proposed that iOPN contributes to protection and sOPN is involved in promotion of the disease . The last but not the least possible reason is that OPN expression is predominant in areas with active fibrogenesis and where myofibroblasts are accumulated, as confirmed by the histological analysis .…”
Section: Discussionmentioning
confidence: 75%
“…The second reason may be due to the fact that OPN is altered by posttranscriptional modification, splicing, and cleavage . Two isoforms of OPN, intercellular OPN (iOPN) and secreted OPN (sOPN), exert distinct functions, despite similarities in the molecular structure . iOPN is a cytoskeletal protein that plays a significant role in the regulation of the intracellular protein functions, while sOPN acts as a cytokine .…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that OPN may protect against chronic alcoholic liver injury by blocking the gut-derived LPS and TNF-α in the liver 34 . These discrepancies could be explained, in part, by differences in the models being studied (i.e., varying degrees of severity, duration, gender) and possibly by the different forms of OPNs (i.e., the intracellular OPN isoform [iOPN] and the extracellular/soluble cytokine [sOPN]) 35 .…”
Section: New Insights Into the Underlying Mechanisms Of Chronic-plus-mentioning
confidence: 99%
“…Additionally, alcohol intake induces ER stress followed by the production of proinflammatory mediators and DAMPs that activate the nuclear translocation of cyclic AMP response element-binding protein H (CREBH) and nCREBH [ 10 ]. Another consequence of ER stress is the activation of lipogenic pathways in hepatocytes, particularly through SREBPs, followed by the upregulation of the predominant form of FSP27-β [ 109 , 110 ]. The interaction of FSP27 with lipid droplet membrane proteins promotes lipid droplet formation and steatosis.…”
Section: Pathogenesis Of Aldmentioning
confidence: 99%